(untitled) (Physical Education, Health and Social Sciences, 2025)
The study aimed to examine the parenting styles of parents with children with neurodevelopmental disorders in Karachi, Pakistan. It focused on examining the parenting approach the parents who had children with neurodevelopmental disorders were most likely to practice in their parenting journey and the approach they were less inclined towards, and to analyze the parent-child relationship among them; in terms of establishing routines, engaging in activities together, strategies used to cope up challenging behaviors and ways of communications used by them. The participants included children with different disability levels, and their families represented a range of socio-economic backgrounds from middle to lower class. The research employed semi-structured interviews and online questionnaires to gather data, Permissive parenting style was the most common, followed by authoritarian and authoritative styles. The use of gestures and signs as communication methods was prevalent among parents, with limited use of visual aids. Challenges in maintaining rules and discipline were observed among parents. This research highlights the importance of providing support and resources to parents of children with neurodevelopmental disorders, particularly in enhancing communication methods and establishing consistent rules. By addressing these areas, practical solutions can be generated to these challenges.